AIEgen-loaded nanofibrous membrane as photodynamic/photothermal antimicrobial surface for sunlight-triggered bioprotection. (September 2021) - Li, Meng; Wen, Haifei; Li, Haoxuan; Yan, Zhi-Chao; Li, Ying; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract: The outbreak of infectious diseases such as COVID-19 causes an urgent need for abundant personal protective equipment (PPE) which leads to a huge shortage of raw materials. Additionally, the inappropriate disposal and sterilization of PPE may result in a high risk of cross-contamination. Therefore, the exploration of antimicrobial materials possessing both microbe interception and self-decontamination effects to develop reusable and easy-to-sterilize PPE is of great importance. Herein, an aggregation-induced emission (AIE)-active luminogen-loaded nanofibrous membrane (TTVB@NM) sharing sunlight-triggered photodynamic/photothermal anti-pathogen functions are prepared using the electrospinning technique. Thanks to its porous nanostructure, TTVB@NM shows excellent interception effects toward ultrafine particles and pathogenic aerosols. Benefiting from the superior photophysical properties of the AIE-active dopants, TTVB@NM exhibits integrated properties of wide absorption in visible light range, efficient ROS generation, and moderate photothermal conversion performance. A series of antimicrobial evaluations reveal that TTVB@NM could effectively inactivate pathogenic aerosols containing bacteria (inhibition rate: >99%), fungi ( 88%), and viruses (>99%) within only 10 min sunlight irradiation. This study represents a new strategy to construct reusable and easy-to-sterilize hybrid materials for potential bioprotective applications.